Most diverse, most neglected: weevils (Coleoptera: Curculionoidea) are ubiquitous specialized brood-site pollinators of tropical flora - Haran, Julien; Kergoat, Gael J.; de Medeiros, Bruno A. S. (Peer Community Journal)

(untitled)
In tropical environments, and especially tropical rainforests, a major part of pollination services is provided by diverse insect lineages. Unbeknownst to most, beetles, and more specifically hyperdiverse weevils (Coleoptera: Curculionoidea), play a substantial role there as specialized mutualist brood pollinators. The latter contrasts with a common view where they are only regarded as plant antagonists. This study aims to provide a comprehensive understanding of what is known about plant-weevil brood-site mutualistic interactions, through a review of the known behavioral, morphological and physiological features found in these systems, and the identification of potential knowledge gaps. To date, plant-weevil associations have been described or indicated in no less than 600 instances. Representatives of major plant lineages are involved in these interactions, which have emerged independently at least a dozen times. Strikingly, these mutualistic interactions are associated with a range of convergent traits in plants and weevils. Plants engaged in weevil-mediated pollination are generally of typical cantharophilous type exhibiting large, white and fragrant flowers or inflorescences and they also show specific structures to host the larval stages of their specialist pollinators. Another characteristic feature is that flowers often perform thermogenesis and exhibit a range of strategies to separate sexual phases, either spatially or temporally. Conversely, lineages of brood-site weevil pollinators present numerous shared behavioral and physiological traits, and often form multispecific assemblages of closely related species on a single host; recent studies also revealed that they generally display a high degree of phylogenetic niche conservatism. This pollination mutualism occurs in all tropical regions, and the contrasts between the known and expected diversity of these systems suggests that a wide range of interactions remain to be described globally. Our early estimates of the species richness of the corresponding weevil clades and the marked pattern of phylogenetic niche conservatism of host use further suggest that weevil-based pollination far exceeds the diversity of other brood-site mutualistic systems, which are generally restricted to one or a few groups of plants. As such, weevil pollinators constitute a relevant model to explore the emergence and evolution of specialized brood-site pollination systems in the tropics.